Knowledge and Associated Factors of Postpartum Contraceptive Use Among Women in the Extended Postpartum Period in Gondar City, Northwest Ethiopia - Mekonnen BD; Gelagay AA; Lakew AM (Dove Medical Press, 2021)
Birye Dessalegn Mekonnen,1 Abebaw Addis Gelagay,2 Ayenew Molla Lakew3 1Department of Nursing, Teda Health Science College, Gondar, Ethiopia; 2Department of Reproductive Health, Institute of Public Health, College of Medicine and Health Science, University of Gondar, Gondar, Ethiopia; 3Department of Epidemiology and Biostatistics, Institute of Public Health, College of Medicine and Health Science, University of Gondar, Gondar, EthiopiaCorrespondence: Birye Dessalegn Mekonnen Email birye22@gmail.comBackground: The choice of a postpartum contraceptive method and the timing of its initiation depend on the woman’s knowledge regarding postpartum contraceptives use. Also, women’s perception towards family planning is reliant on good knowledge and has a great influence on their attitudes and practices. There is limited information on the knowledge and associated factors of postpartum contraceptive use among women. Therefore, the aim of this study was to assess the knowledge and associated factors of postpartum contraceptive use among women in the extended postpartum period.Methods: An institutional-based cross-sectional study was conducted from November 5, 2018 to December 5, 2018 among postpartum women in six health institutions in Gondar city, northwest Ethiopia. A systematic random sampling technique was used to select the study participants. Data were analyzed using SPSS version 20. Bivariable and multivariable logistic regression models were fitted to identify the determinants of knowledge of postpartum contraceptive use. Adjusted odds ratio (AOR) with their 95% confidence intervals (CI) were calculated. P-values less than 0.05 were considered to indicate statistical significance.Results: Out of 403 participants, 299 (74.2%) had good knowledge on postpartum contraceptive use. Being urban residents (AOR=2.95, 95% CI=1.34– 6.48), previous modern contraceptives use (AOR=5.15, 95% CI=1.16– 22.88), health facility delivery (AOR=4.10, 95% CI=1.20– 13.98), and counseling about family planning during PNC (AOR=3.80; 95% CI=1.52– 9.51) were significantly associated with good knowledge.Conclusion: This study showed that the knowledge of women regarding postpartum contraceptives was relatively low. Therefore, increasing institutional delivery service and counseling about family planning during the postpartum period should get more focus to address the knowledge gap of postpartum mothers.Keywords: knowledge, postpartum, contraceptives use, Ethiopia